Clinical Validation of the UKMS Register Minimal Dataset utilising Natural Language Processing. (2017) - Middleton, Rod; Akbari, Ashley; Lockhart-Jones, Hazel; Jones, Jemma; Owen, Charlotte; Hughes, Stella; Gain, Richard; Ford, David
No abstract available